Berfilsafat Dalam Pendidikan Islam: Tafsir Ayat-Ayat Al-Quran Tentang Mencari Kebenaran Dan Mengembangkan Pengetahuan - Taufik Mukmin; Nurlila Kamsi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
The practice of modern Islamic education today tends to be stuck in administrative formalities so as to lose the philosophical and reflective depth that is the essence of the teachings of the Qur'an. This research aims to explore the philosophical dimension in the Qur'an to reconstruct the Islamic education model that is able to harmonize revelation with the development of reason. This study uses a qualitative method through a literature study with thematic interpretation analysis (maudhu'i) on key terms such as al-haqq, al-'ilm, and hikmah. The results of the study show that philosophy in Islam is an instrument to harmonize reason and faith through the process of tafakkur and tadabbur. Islamic epistemology positions revelation as a guide of reason in achieving absolute truth. In the context of education, this integration aims to form students who have spiritual depth (ma'rifah) and a solid understanding of religion (tafaqquh fi al-din), so that education is not only a cognitive process, but also transformative for character and intellectual.